IL-19 Up-Regulates Mucin 5AC Production in Patients With Chronic Rhinosinusitis via STAT3 Pathway - Lai, Xiaoping; Li, Xia; Chang, Lihong; Chen, Xiaohong; Huang, Zizhen; Bao, Hongwei; Huang, Jiancong; Yang, Luoying; Wu, Xifu; Wang, Zhiyuan; Bellanti, Joseph A.; Zheng, Song Guo; et al. (Frontiers in Immunology, 2019)
The mucin gene MUC5AC is highly expressed both in chronic respiratory inflammatory diseases and inflammatory bowel disease where mucin secretion is regulated by members of the interleukin IL-20 subfamily. This study was conducted to determine the roles and mechanisms of IL-19, a member of the IL-20 subfamily, in regulating MUC5AC production in chronic rhinosinusitis (CRS). We analyzed the expression of mucin and MUC5AC in the nasal mucosa of patients with CRS by periodic acid Schiff (PAS) staining and immunohistochemical examination. Real-time quantitative PCR, ELISA, confocal microscopy and western blotting were used to measure MUC5AC expression in primary human nasal epithelium cells (PHNECs) stimulated with recombinant human IL-19 (rhIL-19), IL-19 receptor siRNA transfection or control. The involvement of the STAT3 signaling pathway was examined by the use of cryptotanshinone (CRY, an inhibitor of STAT3). Mucin and MUC5AC were significantly increased in mucosa of CRS with/without nasal polyps compared to mucosa isolated from control who had no CRS, but there were no significant differences between these two groups. Pretreatment with rhIL-19 up-regulated the expression of MUC5AC levels in PHNECs. Knockdown of IL-20R2 and pretreatment with CRY attenuated MUC5AC production induced by rhIL-19. We propose that IL-19 up-regulates MUC5AC-induced mucin production via the STAT3 pathway in CRS, highlighting the important role IL-19 may play in mucin production in chronic respiratory diseases.